Assessing the 2004–2018 Fentanyl Misusing Issues Reported to an International Range of Adverse Reporting Systems - Schifano, Fabrizio; Chiappini, Stefania; Corkery, John Martin; Guirguis, Amira (Frontiers in Pharmacology, 2019)
Objective: A recent, global, increase in the use of opioids including the prescribing, highly potent, fentanyl has been recorded. Due its current popularity and the potential lethal consequences of its intake, we aimed here at analysing the fentanyl misuse, abuse, dependence and withdrawal-related adverse drug reactions (ADRs) identified within the European Medicines Agency (EMA); the UK Yellow Card Scheme (YCS); and the US Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) databases. Methods: Descriptive analysis of both ADRs and related cases. Results: The analysis of fentanyl-related misuse, abuse, dependence and withdrawal cases reported during years 2004-2018 to the EMA; the YCS; and the FAERS showed increasing levels overtime; specifically, EMA-related data presented two peaks (e.g. in 2008 and 2015), whilst the FAERS dataset was characterised by a dramatic increase of the ADRs collected over the last 18 months, and particularly from 2016. Some 127,313 ADRs (referring to n=6,161 patients/single cases) related to fentanyl’s misuse/abuse/dependence/withdrawal issues were reported to EMA, with 14,287 being judged by the reporter as ‘suspect’. The most represented ADRs were: ‘drug dependence’ (76.87%); ‘intentional product misuse’ (13.06%); and ‘drug abuse’ (7.45%). Most cases involved adult males and the concomitant use of other prescribing/illicit drugs. A range of idiosyncratic (i.e. ingestion/injection of transdermal patches’ fentanyl) and very high-dosage intake cases were here identified. Significant numbers of cases required either a prolonged hospitalization (192/559=34.35%) or resulted in death (185/559=33.09%). Within the same time frame, YCS collected some 3,566 misuse/abuse/dependence/withdrawal ADRs, corresponding to 1,165 single patients/cases, with those most frequently reported being ‘withdrawal’; ‘intentional product misuse’; and ‘overdose’ ADRs. Finally, FAERS identified a total of 19,145 misuse/abuse/dependence/withdrawal-related cases, being ‘overdose’; withdrawal; and ‘drug use disorder/drug abuse/drug diversion’ the most represented ADRs (respectively 43.11%; 20.80; 20.29%). Conclusions: Fentanyl abuse may be considered a public health issue with significant implications for clinical practice. Spontaneous pharmacovigilance reporting systems should be considered for mapping new trends of drug abuse.